Effect of Ultrasound-Guided Lumbar Plexus Block on Perioperative Analgesia in Children Undergoing Proximal Fracture Femur Surgeries - Abdellah Ahmed, Gad Sayed Gad, Abbady; Sayed, Zeinab Mustafa; Mohamed, Mohamed Abdelaziz (Journal of Neonatal Surgery, 2025)
Children's proximal femur fractures are uncommon, representing below one percent of all children's fractures, and are commonly because of high-energy trauma. These injuries pose significant diagnostic and therapeutic challenges due to their anatomical complexity and the possibility of complications like avascular necrosis. Prompt diagnosis, appropriate classification—most commonly via the Delbet system—and early anatomical reduction are crucial for optimal outcomes. Fixation strategies vary by age, fracture type, and displacement, often involving smooth pins, cannulated screws, or pediatric sliding hip screws. Effective perioperative pain management is essential in these patients to improve recovery, minimize opioid use, and reduce hospital stay. The lumbar plexus block (LPB), although traditionally underused in children due to anatomical depth and technical complexity, has gained attention with the advent of ultrasound-guided techniques. The lumbar plexus, positioned deep within the psoas muscle, innervates the hip, thigh, and knee via its major branches. Ultrasound-guided LPB, especially with the "Shamrock method," enhances needle placement accuracy and decreases the possibility of complications like vascular puncture or nerve injury. When combined with general anesthesia or other regional techniques, LPB provides superior analgesia and improved patient satisfaction in pediatric proximal femur surgery. This review outlines the current understanding of pediatric proximal femoral fractures, their management, and the evolving role of ultrasound-guided LPB in enhancing perioperative care.